Ideologi dan Kelas Sosial Pengarang dalam Novel Matinya Sang Penguasa Karya Nawal el Sadawi: Kajian Sastra Marxis - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This research is based on thought that the novel is an imitation or reflection of society (mimetis). There are motives, purpose, and messages the author wishes to convey through his opus. The object of this research is the novel Matinya Sang Penguasa (MSP) by Nawal el Sadawi. In the MSP, there is a social gap between the rich and the poor, and between the ruler and the people. Class gap and this social class contradiction enter domain sociology of literature, especially Marxist literature. This research aims to answer the problem how social aspects, Like the social class structure, the novel relationship with society, and the author's position or ideology that exists in the novel MSP. The results show that there is a social class contrast in the novel MSP. The upper social class is represented by the ruler (Walidesa), while the lower social class is represented by the people (Zakeya). The author's position and ideology appears in the lower classes, which seeks to fight for its rights and against the arbitrariness of the (authoritarian) authorities. This authoritarian ruler then elicits resistance from the people. The fight between the ruler and the people was won by the people.